Throughput Time Optimization in a Production Flow : A Case Study in the Power Wheelchairs Industry - Gustafsson, Malin; Vedin, Elin (2016)
This report is a master thesis conducted during the spring semester of 2016 as a final part of the Masterof Science in Industrial Design Engineering at Luleå University of Technology. The aim of thisthesis was to map and analyze the production flow of Permobil in Timrå, Sweden. This was done inorder to deliver concrete solution proposals in the end of the project, which lay within the Lean philosophyand are adapted to Permobil’s production categorized as high-mix and low-volume products.The overall objective has been to optimize Permobil’s production flow in order to reduce the throughputtime for their products.Permobil is a world leading manufacturer of electrical wheelchairs. Their vision is to stand up for theircostumers’ rights and provide the best possible solutions. For Permobil Timrå to be able to follow thedemand and increase its annual production from the current annual 4,600 chairs to an annual of 7,700chairs in 2018, the production must be more effective. Since the production in Timrå is characterizedby a high-mix and low-volume, problems can occur when reducing throughput time since provenmethods are not always suitable for this type of production.Implementation of the thesis has followed a cyclical approach through the project circle. To create abasic understanding of the work, a theoretical framework was conducted containing subjects as LeanProduction, challenges of implementing Lean, high-mix and low-volume, work in progress and pushand pull system. Mapping and analyzing the current situation was carried out through observations,unstructured interviews, a Deviation Analysis and Value stream mapping. The analysis resulted in arequirement specification that pointed on the requirements of future solutions would come to meet.The main requirements were estimated to good physical and psychological work environment, meetthe customer´s need and increased product flow. Workshops and brainstorming has been used to developand evaluate solution proposals.The mapping and the analysis of the current state show ...